Implementasi Akad Mudharabah Pada Usaha Tambak Ikan Bandeng Dalam Perspektif Hukum Ekonomi Syariah di Desa Bonto Manai Kabupaten Pangkep - Anhar, Natasya Wilda; Lawang, Hasanna; Rachana, Syarifa; Hasibuddin, M.; Arsyad, Yusri Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research discusses the implementation of the mudharabah contract in milkfish pond farming from the perspective of Islamic economic law in Bonto Manai Village, Pangkep Regency. There are two main issues examined in this study: first, to understand the practice of milkfish pond farming in Bonto Manai Village, Pangkep Regency; and second, to analyze how the mudharabah contract is implemented in this business from the perspective of Islamic economic law.This study uses a qualitative descriptive method with a phenomenological approach. Data were collected through observation, semi-structured interviews with informants (residents of Bonto Manai Village involved in milkfish pond farming). The results show that the practice of milkfish pond farming in Bonto Manai Village is carried out in a traditional yet structured manner, including pond drying, liming, fertilization, water intake, seed stocking, daily maintenance, and harvesting after 3–4 months. The implementation of the mudharabah contract in this business is done orally, without a written agreement, based on mutual trust between the capital provider (shahibul maal) and the manager (mudharib). Profit-sharing varies between 50:50 or 60:40, depending on the agreement and the contribution of each party. Profits are divided after deducting operational costs. Losses caused by external factors are borne by the capital owner, while losses due to the negligence of the manager are their moral and material responsibility.